CONCEPT OF FIT DI RUANG TUNGGU PASIEN RAWAT JALAN RUMAH SAKIT UMUM - , Yanuarius Benny Kristiawan ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Concept of fit as a thorough understanding of the modification of behavior patterns and changes in space and its elements has to find a fit condition. This research focusing on fit characteristics that occur in outpatient waiting rooms of public hospitals. Understanding the concept of fit characteristics that occur in space, involves the extent to which aspects of pattern of behavior and pattern of physical environment contribute to achieving fit, so that activities that occur can run stable. The research was conducted in an outpatient waiting room at Panti Nugroho Hospital, Santa Elisabeth Hospital and Panti Rini Hospital in Yogyakarta. Research method used in this study is the rationalistic method. Research variables are: a) the organization, b) the individual, and c) the physical setting. Unit analysis of the samples selected with random in the clinic waiting room at the three hospitals, purposively. Adjustments behaviors of visitor in waiting rooms are: a) adaptation by adjustment, b) adaptation by withdrawal c) adaptation by reaction. The samples are distributed in three-outpatient waiting room at the three hospitals that have been determined. The results showed that the concept of fit as a definition of the space function quality in the outpatient waiting rooms at public hospitals, are strongly influenced by the characteristic of physical environment pattern, where quality is determined by its physical layout, which consists of aspects of form-space, circulation and interior elements. Spatial organization, the degree of closure, the configuration of path of the circulation and furniture arrangements is aspects of the physical order patterns that determine the characteristic of the concept of fit. Characteristic of physical environment pattern that occur, related with the pattern of behavior in which behavioral adaptation by adjustment that motivated by emotional and problem-solving behavior becomes the dominant aspects.